Design and Construction of a Comprehensive Digital Security System - Akpiri B; Ezeonye C; Nwokeafor J; Odo G; Ukoima K (Journal of Electronic Design Engineering, 2019)
This paper presents the design and construction of a comprehensive digital security system with the aim of providing a 24 hour digital watchdog for institutions such as banks, schools, the church, residential homes or anything that requires monitoring. The infra-red and digital technologies were used in the realization of this objective. The infra-red (I.R.) signal is transmitted by an I.R diode which is intercepted and decoded by the receiver circuitry. Obstructing the line of sight (within 8 meters) produced a digital display of the zone trespassed. This also triggers an alarm, both of which are designed to have duration of 30 seconds. The transmitters and sensors should be raised at least 1 meter above the ground to ensure that only humans trigger the alarm.